2022
DOI: 10.1073/pnas.2106843119
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety of human environments can be supported by effective use of renewable biomass

Abstract: Preventing pathogenic viral and bacterial transmission in the human environment is critical, especially in potential outbreaks that may be caused by the release of ancient bacteria currently trapped in the permafrost. Existing commercial disinfectants present issues such as a high carbon footprint. This study proposes a sustainable alternative, a bioliquid derived from biomass prepared by hydrothermal liquefaction. Results indicate a high inactivation rate of pathogenic virus and bacteria by the as-prepared bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Also, aeration facilitates the proliferation of innate microorganisms present in compost feedstocks that can compete or act as predators of pathogens in compost [ 30 ]. Another explanation for the slower inactivation of ASFv using sawdust is the presence of natural compounds, such as polyphenols, which can inhibit aerobic microbial activities [ 31 ]. Alternatively, a study by Erickson et al [ 32 ] suggested that phenolics produced during the degradation of lignin influenced pathogen inactivation in compost.…”
Section: Discussionmentioning
confidence: 99%
“…Also, aeration facilitates the proliferation of innate microorganisms present in compost feedstocks that can compete or act as predators of pathogens in compost [ 30 ]. Another explanation for the slower inactivation of ASFv using sawdust is the presence of natural compounds, such as polyphenols, which can inhibit aerobic microbial activities [ 31 ]. Alternatively, a study by Erickson et al [ 32 ] suggested that phenolics produced during the degradation of lignin influenced pathogen inactivation in compost.…”
Section: Discussionmentioning
confidence: 99%
“…The capillary column-introduced voltage was 3.8 kV, and the accumulating time was 0.06 s. The signal-to-noise ratio was enhanced by accumulating 300 scans. Then, the statistics were analyzed to calculate the intensity weighted average values of O/C, H/C, DBE, and m / z for observing the transformation of the main chemical component of the samples. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Then, the statistics were analyzed to calculate the intensity weighted average values of O/C, H/C, DBE, and m/z for observing the transformation of the main chemical component of the samples. 24,25 As for gaseous products, the samples were analyzed by gas chromatography (GC) (PerkinElmer Clarus 580) to identify the composition. The proportion and volume of smallmolecule gases (such as H 2 , CO, CO 2 , C 2 H 2 , C 2 H 4 , C 2 H 6 , C 3 H 6 , and C 3 H 8 ) were calculated to investigate the relationship between the FJH input power and the component changes.…”
Section: Assessment Of the Fjh-derived Productsmentioning
confidence: 99%
“…In order to increase the economic viability, some researchers attempted to use the aqueous phase for microalgae cultivation or recycle the aqueous phase back to the HTL process with the aim to increase biocrude yield/quality (Chen et al, 2022). Recently, the aqueous phase has been reported to exhibit antibacteria/virus activities (Yu et al, 2022). A process intensification technique, microwave irradiation, was also applied for HTL biocrude production (Yang et al, 2020b).…”
Section: Suitability Of Hydrothermal Liquefactionmentioning
confidence: 99%